On growth-optimal tax rates and the issue of wealth inequalities. (13th November 2015) - Bouchaud, Jean-Philippe
Abstract: We consider a highly stylized, yet non trivial model of the economy, with a public and private sector coupled through a wealth tax and a redistribution policy. The model can be fully solved analytically, and allows one to address the question of optimal taxation and of wealth inequalities. We find that according to the assumption made on the relative performance of public and private sectors, three situations are possible. Not surprisingly, the optimal wealth tax rate is either 0% for a deeply dysfunctional government and/or highly productive private sector or 100% for a highly efficient public sector and/or debilitated/risk averse private investors. If the gap between the public/private performance is moderate, there is an optimal positive wealth tax rate maximizing economic growth, even—counter-intuitively—when the private sector generates more growth. The compromise between profitable private investments and taxation, however, leads to a residual level of inequalities. The mechanism leading to an optimal growth rate is akin to the well-known explore/exploit trade-off.